2016
DOI: 10.1016/j.jaci.2016.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Controlled diesel exhaust and allergen coexposure modulates microRNA and gene expression in humans: Effects on inflammatory lung markers

Abstract: Expression of specific miRNAs and genes associated with bronchial immune responses were significantly modulated by DE or allergen. However, DE did not augment the effect of allergen at 48 hours, suggesting that adjuvancy may be transient or require higher or prolonged exposure. In silico analysis suggested a possible mechanism contributing to epithelial wall damage following allergen exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 64 publications
2
44
0
Order By: Relevance
“…Epithelial damage is reported with human DE exposure (including particles and gases) versus clean air (100, 101). The same authors showed an interaction with glutathione- S -transferase theta-1 and DE in the activation of cytotoxic T cells in lung lavage, and in the development of airflow limitation (with glutathione- S -transferase theta-1-null plus DE exposure) (100).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial damage is reported with human DE exposure (including particles and gases) versus clean air (100, 101). The same authors showed an interaction with glutathione- S -transferase theta-1 and DE in the activation of cytotoxic T cells in lung lavage, and in the development of airflow limitation (with glutathione- S -transferase theta-1-null plus DE exposure) (100).…”
Section: Methodsmentioning
confidence: 99%
“…The same authors showed an interaction with glutathione- S -transferase theta-1 and DE in the activation of cytotoxic T cells in lung lavage, and in the development of airflow limitation (with glutathione- S -transferase theta-1-null plus DE exposure) (100). An epithelial epigenetic effect has been shown: acute exposure to DE and/or allergen alters expression of microRNA and genes, with effects on inflammatory markers associated with asthma (101, 102). There are methylation changes in airway epithelium after acute DE exposure, and exposure–exposure epigenetic interactions caused by DE with allergen exposure.…”
Section: Methodsmentioning
confidence: 99%
“…For example, gene–environment interactions have been demonstrated with changes in microRNA [3] and bronchial epithelial DNA methylation, after exposures to diesel exhaust [104]. For individuals with atopy-prone or immune modulated genotypes, environmental exposures play a role in the onset of an allergic disorder [105], including exposures to aeroallergens [2,106].…”
Section: Reviewmentioning
confidence: 99%
“…Air pollutants allow for easier penetration of pollen and spore allergens because they trigger damage to the airway mucociliary clearance mechanisms [128,141]. Particulate matter smaller than 2.5 μm (PM 2.5 ) reaches deeply in the lungs and acts as an adjuvant that increases production of IgE [3,151,152]. Furthermore, exposure to diesel exhaust is known to impact DNA methylation and impaired regulatory T-cell functions, two mechanisms relevant for the immune response [104].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation